Pathogenic mitochondria DNA mutations: current detection tools and interventions - Mustafa, Mohd Fazirul; Fakurazi, Sharida; Abdullah, Maizaton Atmadini; Maniam, Sandra (MDPI, 2020)
Mitochondria are best known for their role in energy production, and they are the only mammalian organelles that contain their own genomes. The mitochondrial genome mutation rate is reported to be 10–17 times higher compared to nuclear genomes as a result of oxidative damage caused by reactive oxygen species during oxidative phosphorylation. Pathogenic mitochondrial DNA mutations result in mitochondrial DNA disorders, which are among the most common inherited human diseases. Interventions of mitochondrial DNA disorders involve either the transfer of viable isolated mitochondria to recipient cells or genetically modifying the mitochondrial genome to improve therapeutic outcome. This review outlines the common mitochondrial DNA disorders and the key advances in the past decade necessary to improve the current knowledge on mitochondrial disease intervention. Although it is now 31 years since the first description of patients with pathogenic mitochondrial DNA was reported, the treatment for mitochondrial disease is often inadequate and mostly palliative. Advancements in diagnostic technology improved the molecular diagnosis of previously unresolved cases, and they provide new insight into the pathogenesis and genetic changes in mitochondrial DNA diseases.